2023
DOI: 10.1021/acsami.3c12048
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Strength of Metal Ion-Doped MXene-Based Double-Network Hydrogels for Highly Sensitive and Durable Flexible Sensors

Qin Yang,
Mingzi Li,
Rong Chen
et al.

Abstract: Development of conductive hydrogels with high sensitivity and excellent mechanical properties remains a challenge for constructing flexible sensor devices. Herein, a universal strategy is presented for enhancing the mechanical strength of Mxene-based double-network hydrogels through metal ion coordination effects. Polyacrylamide (PAM)/sodium alginate (SA)/Mxene double-network (PSM-DN) hydrogels were prepared by metal ion impregnation of PAM/SA/Mxene (PSM) hydrogels. High electrical conductivity is achieved due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…As shown in Figure A–C, the elongation at break of the hydrogels increases with increasing MXene contents (0–4%). The toughness and Young’s modulus of the hydrogels also show an increasing trend, where Young’s modulus is similar to human tissue (0–100 kPa). , When the content of MXene increases from 0 to 4%, it can be found that its fracture stress increases from 17.6 to 61.9 kPa. This is because the MXene nanosheets contain many functional groups, which cross-link with the hydrogel matrix, so that the MXene nanosheets can be successfully dispersed uniformly in the polymer network.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…As shown in Figure A–C, the elongation at break of the hydrogels increases with increasing MXene contents (0–4%). The toughness and Young’s modulus of the hydrogels also show an increasing trend, where Young’s modulus is similar to human tissue (0–100 kPa). , When the content of MXene increases from 0 to 4%, it can be found that its fracture stress increases from 17.6 to 61.9 kPa. This is because the MXene nanosheets contain many functional groups, which cross-link with the hydrogel matrix, so that the MXene nanosheets can be successfully dispersed uniformly in the polymer network.…”
Section: Resultsmentioning
confidence: 76%
“…As a two-dimensional inorganic material composed of transition metal carbides and nitrides, MXene has a unique structure and compelling properties such as excellent conductivity, high surface area, tunable surface functional groups, and outstanding hydrophilicity. , Furthermore, MXene has chemical stability, which makes it an ideal conductive material, and is widely used by researchers in flexible sensors, , supercapacitors, catalysts, , and electromagnetic interference. , However, MXene hydrogel exhibits a low elongation at break, which leads to easy damage during stretching. Additionally, its elastic modulus is not compatible with human tissues, limiting its practical applications in flexible sensors.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The addition of CNC as nano-level toughening fillers to PAM-based hydrogels can effectively improve the energy dissipation of the polymer through interfacial interaction, thus improving the mechanical strength of the hydrogel and endowing it with a high solution absorption capacity while maintaining its structural integrity. 16,17 Multiwalled carbon nanotubes (MWCNTs) are widely used as nanofillers to prepare conductive composite hydrogels because of their excellent electrical conductivity, physical and mechanical properties, and chemical stability, and high elastic modulus. 18,19 Hydrogels contain a lot of water, so they inevitably freeze or evaporate, which makes them lose their flexibility, greatly hindering their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen et al incorporated GO/carbon nanotubes (CNT) into sodium alginate hydrogels, producing hydrogels with good conductivity and flame-retardant properties, enabling them to exhibit effective alarm response in flame environments. Additionally, the carboxyl groups in PAM can interact with multivalent cations (such as Ni 2+ ), thereby enhancing the mechanical strength of the hydrogel network . When GO is mixed with monomers, physical interactions such as hydrogen bonding, hydrophobic interactions, and metal complexation occur between the monomer or hydrophilic polymer chains and the surface of GO, thereby improving the strength, toughness, and thermal responsiveness of the hydrogel. , In situations of exceptionally high temperatures or flame attacks, the functional groups on GO undergo thermal decomposition, forming reduced graphene oxide (rGO) with good conductivity .…”
Section: Introductionmentioning
confidence: 99%